Leakage Proof, Flame-Retardant, and Electromagnetic Shield Wood Morphology Genetic Composite Phase Change Materials for Solar Thermal Energy Harvesting - Chen, Yuhui; Meng, Yang; Zhang, Jiangyu; Xie, Yuhui; Guo, Hua; He, Mukun; Shi, Xuetao; Mei, Yi; Sheng, Xinxin; Xie, Delong (Nano-Micro Letters, 2024)
Phase change materials (PCMs) offer a promising solution to address the challenges posed by intermittency and fluctuations in solar thermal utilization. However, for organic solid–liquid PCMs, issues such as leakage, low thermal conductivity, lack of efficient solar-thermal media, and flammability have constrained their broad applications. Herein, we present an innovative class of versatile composite phase change materials (CPCMs) developed through a facile and environmentally friendly synthesis approach, leveraging the inherent anisotropy and unidirectional porosity of wood aerogel (nanowood) to support polyethylene glycol (PEG). The wood modification process involves the incorporation of phytic acid (PA) and MXene hybrid structure through an evaporation-induced assembly method, which could impart non-leaking PEG filling while concurrently facilitating thermal conduction, light absorption, and flame-retardant. Consequently, the as-prepared wood-based CPCMs showcase enhanced thermal conductivity (0.82 W m−1 K−1, about 4.6 times than PEG) as well as high latent heat of 135.5 kJ kg−1 (91.5% encapsulation) with thermal durability and stability throughout at least 200 heating and cooling cycles, featuring dramatic solar-thermal conversion efficiency up to 98.58%. In addition, with the synergistic effect of phytic acid and MXene, the flame-retardant performance of the CPCMs has been significantly enhanced, showing a self-extinguishing behavior. Moreover, the excellent electromagnetic shielding of 44.45 dB was endowed to the CPCMs, relieving contemporary health hazards associated with electromagnetic waves. Overall, we capitalize on the exquisite wood cell structure with unidirectional transport inherent in the development of multifunctional CPCMs, showcasing the operational principle through a proof-of-concept prototype system. Highlights: 1 An innovative class of versatile form-stable composite phase change materials (CPCMs) was fruitfully exploited, featuring MXene/phytic acid hybrid depositing on non-carbonized wood as a robust support. 2 The wood-based CPCMs showcase enhanced thermal conductivity of 0.82 W m−1 K−1 (4.6 times than polyethylene glycol) as well as high latent heat of 135.5 kJ kg−1 (91.5% encapsulation) with thermal durability and stability throughout at least 200 heating and cooling cycles. 3 The wood-based CPCMs have good solar-thermal-electricity conversion, flame-retardant, and electromagnetic shielding properties.